Cre‐loxP‐Mediated Recombination: General Principles and Experimental Considerations. Issue 1 (2nd March 2017) - McLellan, Micheal A.; Rosenthal, Nadia A.; Pinto, Alexander R.
Abstract : The cre‐ lox P–mediated recombination system (the "cre‐ lox P system") is an integral experimental tool for mammalian genetics and cell biology. Use of the system has greatly expanded our ability to precisely interrogate gene function in the mouse, providing both spatial and temporal control of gene expression. This has been largely due to the simplicity of its use and its adaptability to address diverse biological questions. While the use of the cre‐ lox P system is becoming increasingly widespread, in particular because of growing availability of conditional mouse mutants, many considerations need to be taken into account when utilizing the cre‐ lox P system. This review provides an overview of the cre‐ lox P system and its various permutations. It addresses the limitations of cre‐ lox P technology and related considerations for experimental design, and it discusses alternative strategies for site‐specific genetic recombination and integration. © 2017 by John Wiley & Sons, Inc.